Aspirin administration from early pregnancy versus initiation after 11 weeks of gestation for prevention of pre-eclampsia in high-risk pregnant women: Study protocol for randomized controlled trial - Sedigheh Hantoushzadeh; Arezoo Behzadian; Mohammad Mehdi Hasheminejad; Faezeh Hasheminejad; Alireza Helal Birjandi; Mojtaba Akbari; Marjan Ghaemi (International Journal of Reproductive BioMedicine, 2024)
Abstract Background: Pre-eclampsia (PE) is a multiorgan disorder that affects 2–5% of all pregnant women. Present recommendations for when to start aspirin in high-risk women are after 11 wk of gestation. Objective: We present a protocol to investigate the effectiveness of aspirin use from early pregnancy, which is a randomized controlled trial to assess whether prescribed low-dose aspirin from early pregnancy reduces the prevalence of early and late-onset PE. Additionally, to compare the effectiveness of aspirin administration before and after 11 wk in reducing the occurrence of PE? Materials and Methods: All pregnancies at risk of PE, according to demographic and midwifery history, who are referred to the Maternal-Fetal Clinic of Tehran University hospital, Tehran, Iran were invited to take part in the trial. The outcomes of pregnancy and newborns will be gathered and analyzed. The first registration for the pilot study was in January 2023, and the participants were recognized as high-risk for PE. In addition, enrollment in the main study will begin as of October 2023.